Multiple resistant salmonella in Accra, Ghana - Mills-Robertson, F.C.; Newman, M.J.; Mensah, P.; Addy, M.E. (Ghana Medical Journal, 2003)
A total of 115 Salmonella strains isolated during 1998-1999 in Accra. Ghana were examined for drug/multiple drug resistance, using first-line antityphoid antibiotics. namely, ampicillin (Am). chloramphenicol (Cm), Tetracycline (Te) and Trimethoprim/sulphamethoxazole (Ts). These organisms were isolated from urine, stool, food, cerebrospinal fluid, blood and other sources. The number of organisms isolated from blood alone was 82(71.3%). Eight serological groups were identified and the most common isolates were groups 0 (57 .4%) and B (33%), with the least found in groups A, G and I. Forty-four (38.3%) isolates were found to be sensitive to all four antibiotics whilst 71 (61.7%) were resistant to one or more of the antibiotics used. Thirteen (11.3%) of the resistant strains were resistant to only one of the antibiotics, 6 (5.2%) were resistant to two of the antibiotics, 22 (19.1 %) were resistant to three of the antibiotics, and 30 (26.1 %) were resistant to all four of the antibiotics used. All the organisms were however, sensitive to Ciprofloxacin n, and Ceftriaxone and Gentamicin. These findings indicated that multiple resistant Salmonella arc prevalent in Ghana and national surveillance to determine the level of resistance is needed for the nation.
Journal Article
Keywords: Antibiotic susceptibility; multiple resistance; Salmonella